Downregulation of miR-574-5p inhibits HK-2 cell viability and predicts the onset of acute kidney injury in sepsis patients. Issue 1 (1st January 2021) - Liu, Shanshan; Zhao, Lishu; Zhang, Li; Qiao, Lujun; Gao, Shufang
Abstract: Background: Increased levels of microRNA-574-5p (miR-574-5p) have been found to be associated with increased survival of septic patients, indicating the potential role of miR-574-5p in protecting against septic progression and complications. Acute kidney injury (AKI) is one of the most common and serious complications of sepsis. Therefore, the aim of this study was to test these hypotheses: (1) in a renal cell culture line (HK-2), upregulated expression of miR-574-5p increases, and downregulated expression of miR-574-5p decreases cell viability, and (2) serum levels of miR-574-5p from patients with sepsis and AKI are lower than those of patients with sepsis but no AKI. Methods: The expression of miR-574-5p was regulated by cell transfection in HK-2 cells, and HK-2 cell viability was measured using the Cell Counting Kit-8. Serum miR-574-5p expression was analyzed using qRT-PCR. The predictive value of miR-574-5p for AKI onset was evaluated using the receiver operating characteristic curve and logistic regression analysis. Results: The overexpression of miR-574-5p promoted HK-2 cell viability. Fifty-eight sepsis patients developed AKI, who had significantly lower miR-574-5p expression. miR-574-5p expression was decreased with AKI stage increase and correlated with kidney injury biomarker and had relatively high accuracy to predict AKI occurrence from sepsis patients. Conclusion: Overexpression of miR-574-5p in cultured HK-2 cells increases cell viability and knocked-down expression of miR-574-5p decreases cell viability. Consistently, septic patients with AKI were found to have less upregulation of miR-574-5p expression compared to septic patients without AKI. Thus, serum miR-574-5p may provide a novel biomarker for septic AKI.